2021
DOI: 10.30714/j-ebr.2021370083
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Pandemic: A comparison of adult and pediatric populations

Abstract: Couple of pneumonia cases were reported in a short period in Wuhan, China. The cases were revealed to be associated with a different coronavirus type was named SARS-CoV-2 and the disease was identified as Covid-19. It is known that the disease occurs in all age groups. We aimed to evaluate the differences in clinical and laboratory features between adult and pediatric patients. Method: The study is a retrospective cross-sectional study and consists of 206 patients with a definitive diagnosis of Covid-19 confir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…In our study, patients diagnosed with CO-VID-19 experienced the symptoms of weakness, inability to smell/taste, and muscle or joint pain the most (Table 2). A study conducted in Turkey reported that the most common symptoms experienced in patients with COVID-19 were fever, cough, and shortness of breath [21]. A study conducted in China reported that individuals most commonly experience symptoms such as cough, fatigue, and phlegm production [22].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, patients diagnosed with CO-VID-19 experienced the symptoms of weakness, inability to smell/taste, and muscle or joint pain the most (Table 2). A study conducted in Turkey reported that the most common symptoms experienced in patients with COVID-19 were fever, cough, and shortness of breath [21]. A study conducted in China reported that individuals most commonly experience symptoms such as cough, fatigue, and phlegm production [22].…”
Section: Discussionmentioning
confidence: 99%